2015
DOI: 10.1063/1.4922373
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency Schottky junction solar cells by co-doping of graphene with gold nanoparticles and nitric acid

Abstract: We have reported an effective method to enhance the efficiency of graphene-on-Si (Gr/Si) Schottky junction solar cells by co-doping of graphene with Au nanoparticles (NPs) and HNO3. Both Au NPs decoration and HNO3 treatment lead to p-type doping of graphene, and their combination is confirmed to be a more effective approach for achieving the higher work function and enhanced electrical conductivity of graphene. Consequently, the power conversion efficiency of Gr/Si solar cells is increased by 2.6 times, with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…Finally a top-contact to the Si-substrate is established by depositing Ag paste on the exposed areas of the wafer, opportunely scratched to guarantee ohmic contact. The characteristic graphene wrinkles extending across the edge of the trench from the isolated area 19 as well as on the Gr/Si junction area are visible. Gr layer covers the edge of the trench keeping its structural integrity and ensuring electrical contact between the junction area and the contact area on top of the isolation layer.…”
Section: Methodsmentioning
confidence: 99%
“…Finally a top-contact to the Si-substrate is established by depositing Ag paste on the exposed areas of the wafer, opportunely scratched to guarantee ohmic contact. The characteristic graphene wrinkles extending across the edge of the trench from the isolated area 19 as well as on the Gr/Si junction area are visible. Gr layer covers the edge of the trench keeping its structural integrity and ensuring electrical contact between the junction area and the contact area on top of the isolation layer.…”
Section: Methodsmentioning
confidence: 99%
“…[45][46][47][48][49][50] Among them, HNO 3 doping is deemed to be the most commonly used method. 60 Feng et al demonstrated that aer immersing the device in HNO 3 vapor for several seconds, ( Fig. 2a and b).…”
Section: The Optimization Of Graphene/si Solar Cellsmentioning
confidence: 99%
“…For the instability of chemical doping, many researchers tried to dope Gr with physical contact instead. Liu et al covered Gr with Au nanoparticles (NPs) with different sizes for p‐type doping . Together with nitric acid doping, they further enhanced the efficiency of Gr/Si solar cells to 10.2%.…”
Section: Engineering Gr/si Solar Cellsmentioning
confidence: 99%
“…The hole density grew steadily as work function of contacted metal nanoparticles increased, suggesting that work function of metal nanoparticles was the reason for physical doping. Kim et al doped Gr with Au nanoparticles and increased its work function by ≈0.15 eV . Doping with Au nanoparticles significantly reduced the ideal factor of Gr/Si solar cells from 3.39 to 1.52, suggesting a much better junction.…”
Section: Engineering Gr/si Solar Cellsmentioning
confidence: 99%